Long-term Treatment Benefits and Prolonged Efficacy of OnabotulinumtoxinA in Patients Affected by Chronic Migraine and Medication Overuse Headache over 3 Years of Therapy - Guerzoni, Simona; Pellesi, Lanfranco; Baraldi, Carlo; Cainazzo, Michela Maria; Negro, Andrea; Martelletti, Paolo; Pini, Luigi Alberto (Frontiers in Neurology, 2017)
Background Chronic migraine affects about the 2% of the general population and it has been recognized as one of the most disabling conditions world-wide by the World Health Organization. Chronic migraine is often associated with the overuse of abortive medication, which determines the worsening of headache itself and the development of a secondary headache called medication overuse headache. The management of these associated conditions is difficult, but a growing amount of evidence is pointing out the effectiveness and the good safety profile of OnabotulinumtoxinA. Despite this, data on OnabotulinumtoxinA effects and safety in long-term use lack. The purpose of the present article is to retrospectively assess the efficacy and safety of OnabotulinumtoxinA in a cohort of chronic migraineurs with drug overuse from the 18th month of treatment until the 3rd year.. Materials and Methods Ninety chronic migraineurs with medication overuse were enrolled between January 2013 and February 2017. All patients were treated with OnabotulinumtoxinA according with PREEMPT dictates. Before every injection session the headache index, the analgesic consumption, the visual analogue scale for pain score, the 36-items short form health survey questionnaire score, the 6-items headache impact test score and the Zung self-rating anxiety and depression scale scores were collected. Adverse events were carefully registered. A simple linear regression was performed to explore the mean changes in the above-mentioned parameters for a single injection session and mean comparison tests were performed using the one-way analysis of variance followed by Tukey-Kramer post-hoc test. Results A significantly improvement for a single injection was registered for all the above-mentioned parameters. Headache index, analgesic consumption, visual analogue pain scale and 6-items headache impact test scores were significantly lower than baseline from the 18th months of treatment onwards. The 36-items short form health survey questionnaire scores were significantly higher than baseline at every injections session from the 18th months onwards. Zung scales didn’t change. No serious adverse events were assessed and no adverse events-related drop-outs were seen. Conclusion OnabotulinumtoxinA effectiveness and safety last until 3 years of therapy, raising the possibility of the use of this therapy even for many years in chronic migraine prevention.